Didactic-methodological procedures for the implementation of the curricular strategies in the higher education - Guillermo Renato Vallejo Portuondo; Neity Mendo Alcolea; Mario Luis Lahera Puig (Centro Provincial de Información de Ciencias Médicas, 2019)
The university vocational training is complex, but the final result of this process should satisfy the social expectative related to the competence of those graduated, reason why the pedagogic sciences should maintain a constant search as for methods, procedures and strategies that allow to satisfy the social responsibility. Keeping in mind the above-mentioned statement the present study was carried out   aimed at contributing to the implementation of the curricular strategies, from a didactic-methodological view, and their fulfillment in an objective way through a process that can be measured and controlled, and the foreseen contents are included in each subject and discipline.